Electroactive layer-by-layer plasmonic architectures based on Au nanorods - Placido, Tiziana (Langmuir : the ACS journal of surfaces and colloids, 2014)
Nanostructured films based on Au nanorods (NRs) have been obtained by layer-by-layer (LbL) assembly driven by electrostatic interaction between metal nanoparticles and polyelectrolytes. Multilayer films have been fabricated by using LbL assembly of poly(sodium styrenesulfonate) (PSS) and positively charged Au NRs on a polyelectrolyte-modified substrate. The effect of fabrication parameters, including the nature of the substrate, the polyelectrolyte initial anchoring layer, and the number of layers has been investigated by means of UV-vis absorbance spectroscopy and atomic force microscopy (AFM). The results demonstrated the dependence of morphology and plasmonic features in the multilayered nanostructured architectures from the nature of the anchoring polyelectrolyte on the substrate, the number of layers, and the kind of NR mutual assembly. In addition, a study of the electrochemical activity at the solid/liquid interface has been carried out in order to assess charge transport through the NR multilayer by using two molecular probes in solution, namely, potassium ferricyanide, a common and well-established redox mediator with reversible behavior, and cytochrome C, a robust model redox protein. The presented systematic study of the immobilization of Au NRs opens the venue to several application areas, such as (bio)chemical sensing